Activation of TRPV1 Contributes to Recurrent Febrile Seizures via Inhibiting the Microglial M2 Phenotype in the Immature Brain - Kong, Weilin; Wang, Xin; Yang, Xingliang; Huang, Wenxian; Han, Song; Yin, Jun; Liu, Wanhong; He, Xiaohua; Peng, Biwen (Frontiers in Cellular Neuroscience, 2019)
Transient receptor potential vanilloid type 1 (TRPV1) is a nonselective cation channel implicated in the nervous system as a key component of several inflammatory diseases. A massive amount of evidence has demonstrated that TRPV1 is extensively expressed in the central nervous system (CNS) and there might be close relationship between TRPV1 and neuroinflammation, which is a crucial pathogenic factor in seizure generation, although it’s signaling mechanism has been less well characterized. Herein, we identified that TRPV1 is functionally expressed in the primary cultured mouse microglia and the membrane expression of TRPV1 is upregulated in rFS mice brain and activated microglia. Stimulation of microglial TRPV1 promoted microglia activation per se and indirectly enhanced seizure susceptibility by inhibiting the neuroprotective effects of microglial transforming growth factor-beta1 (TGF-β1) via interaction with Toll-like receptor 4 (TLR4) in mice. Conversely, TRPV1-/- alleviate hyperthermia or LPS-induced microglial abnormal functional activation and maintained a balanced inflammatory microenvironment in the brain. Taken together, these findings identify that microglial TRPV1, as a potential pro-inflammatory mediator; participate in neuroinflammatory response, which will provide a novel therapeutic strategy for controlling the neuroinflammation-induced seizure.